Pedagogy for the Future in the Context of Nepal: An Exploration with Critical Mathematics Education - Chapai, Krishna Prasad Sharma (Academic Journal of Mathematics Education, 2022)
Critical mathematics education undermines the neutrality of mathematics teaching and learning; it confronts societal barriers and suppression, social justice, and opens up new pathways for students to participate in social and political life. This paper intends to analyze critical mathematics education and how it can be used as a tool to create a bright future for mathematics in Nepal by altering teaching pedagogy and applying it to practice. For this study, the search engine Google, Google scholar, Eric, and ProQuest were used. Three major themes were explored: thoughts of teachers towards critical mathematics education, mathematics education in relation to society, and technology-based teaching. To discuss the result content analysis on the themes were used. This study finds that optimistic attitude, innovation of teachers, and the use of critical pedagogy appear to be too responsible for the bright future of mathematics. To attain the objectives, our teachers must be enthusiastic, knowledgeable about information and technology, and critical and reflective.